Creative Strategies in Indonesian Language Learning: Enhancing Elementary Students’ Writing Skills through Serial Picture Media and the Picture-and-Picture Model - Resma, Pande Komang Resma Permata Dewi; Maria Goreti Rini Kristiantari; Dewi Anzelina (Jurnal Ilmiah Sekolah Dasar, 2025)
The writing skills of third-grade elementary school students are still low. This is due to the use of conventional teaching methods and the lack of digital media in the learning process. This study aims to analyze the effectiveness of serial image media based on the Picture and Picture model in improving the writing skills of third-grade students. The study employed the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The methods and instruments used for data collection included interviews, observations, questionnaires, and essay tests. The research subjects consisted of 11 third-grade students. The data analysis techniques used were qualitative, quantitative, and inferential descriptions. The results of the dependent sample t-test showed a tcount value of 4.86, while the ttable value at a 5% significance level with degrees of freedom (11 – 1) = 10 was 1.795. These results indicate that tcount (4.86) > ttable (1.795), thus H0 is rejected and H1 is accepted. Therefore, it can be concluded that the serial image media based on the Picture and Picture model is effective in improving the writing skills of third-grade students and is suitable for use in learning narrative text material in the Indonesian language subject. The implication of this study is that the serial image media encourages students to be more active in discussing, composing stories, and developing their understanding both independently and in groups.